An Exploratory Study of the Role of Dietary Proteins in the Regulation of Intestinal Glucose Absorption - Dugardin, Camille; Fleury, Léa; Touche, Véronique; Ahdach, Farah; Lesage, Jean; Tenenbaum, Mathie; Everaert, Nadia; Briand, Olivier; Lestavel, Sophie; Ravallec, Rozenn; Cudennec, Benoit (Frontiers in Nutrition, 2022)
Several studies have demonstrated that high protein diets improve glucose homeostasis. Nevertheless, the mechanisms underlying this effect remain elusive. This exploratory study aims to screen and compare the acute effects of dietary proteins from different sources on intestinal glucose absorption. Six dietary proteins from various sources were thus selected and digested thanks to the INFOGEST static gastrointestinal digestion protocol. The digested proteins were able to decrease intestinal glucose absorption in vitro and ex vivo. Moreover, acute ingestion of casein and fish gelatin led to improve glucose tolerance in Wistar rats without significant effect on insulin secretion. In parallel, GLUT2 mRNA expression in enterocytes was decreased following short-term incubation with some of the digested proteins. These results strengthen the evidence that digested protein-derived peptides and amino acids are key regulators of glucose homeostasis and highlight their role in intestinal glucose absorption.